Quais et ouvrages portuaires romains de Rouen/Rotomagus (Seine-Maritime) - Marie-Clotilde Lequoy (Gallia)
The ancient port of Rouen/Rotomagus remains little known despite the discovery of two docks, one situated to the west of the city, and the other to the east. Both are attributed to the 1st c. AD and are located about 150 m north of the present shoreline of the Seine River, at an equivalent altitude. Both rescue operations took place under extremely difficult conditions, in 1979 (dir. D. Halbout-Bertin) and again in 1993 (dir. M.-C. Lequoy). A few older, sporadic discoveries are likely associated with the port and its activities, though uncertainties regarding their exact chronological attribution remain. The city of Rouen was founded on a vast, non-floodable, stony alluvial terrace, measuring approximately 40 ha, and situated at the head of a meander on the concave bank of the Seine. This terrace is framed to the west by the Cailly River Valley and to the east by the Robec and Aubette River Valleys. These waterways facilitated communication with the hinterland located on the plateaus. Indeed, a large overland road mirrors the course of a portion of the waterways, permitting passage through the town. Even before any particular development of the riverbank, it was undoubtedly easy to dock boats along the stony shore. Additionally, the tides, with their alternating currents, would have easily carried ships upstream or downstream. This site seems to have been used very early on, as suggested by the discovery of a Bronze Age dugout canoe, abandoned in a cove to the west of the town, near Place de la Pucelle. A rescue excavation was initiated following the discovery of Gallo-Roman vestiges during the supervision of construction work related to the installation of a metro station. This work took place under extreme and difficult conditions. This included: the need to adapt to the pre-defined construction schedule for the station, the reality of working under concrete slabs, often with insufficient artificial lighting, the forced air supply by a massive, and very noisy air blower, as well as the permanent presence of water and mud due to the rising waters of the Seine despite continuous pumping. The archaeological operation involved an area spanning just over 300 m2 and lasted for a month. Due to a lack of time, the choice was made to mechanise the excavation of structures as much as possible, manually clearing only the most interesting ones and performing only a few manual test-trenches. Almost all of the piles and posts encountered, i.e. around 200, were extracted from the ground with a steam shovel. Thus, Anne Dietrich (Inrap) was able to execute a xylological study, including the observation of all existing traces of wood processing. Vincent Bernard completed a dendrochronological study providing dates from a variety of structures on site, using selections of wood from said constructions. These dates were also corroborated with the help of ceramic dating. A dock was revealed in the southern part of the metro station, spanning its entire width, i.e. approximately 17 m. This dock is located where the gravel of the alluvial terrace begins a steep downward slope. Dendrochronology has revealed two construction periods, a western part, dated to around 5-4 BC, and an eastern part, which was built or rebuilt in the middle of the 1st c. AD. The oldest section of the dock is preserved with a maximum elevation of 0.70 m and a length of about 10 m. This structure presents a mixed external facing, made of medium and large limestone blocks, masoned with clay and sections of oak placed vertically about 1 m to 1.20 m apart from one another. The posts were placed at a depth of 0.25 m to 0.30 m in a peat level revealed by prior digging. They were then wedged with a compact limestone fill, topped with medium to large limestone blocks and sealed with clay. During the excavation, it was observed that the dock was protected from water scouring by an embankment of large stones placed in front of it. This embankment widened in the western part to form a sort of sloping ramp, covered with limestone. On this side, one finds two massive posts, as well as 12 piles carefully arranged in a joined manner so as to form a single load-bearing element. These posts and this composite pile, which form a north-south alignment, perpendicular to the dock, are reminiscent of an important structure (perhaps a wharf). Behind the dock, the bank was stabilized with structures built during the same period. An initial row of three posts, connected to one another by planks, was installed parallel to the dock, at a distance of approximately 6 m. Immediately behind this installation and to the north, a sort of horizontal platform was built, consisting of large limestone blocks resting directly on a gravel level. The height of the grooves for embedding the planks, and the depth at which the posts were buried, suggest that the preserved part likely only corresponds to the foundations of what would have been a box structure. At a distance of 3.50 m to the north, on the gently sloping surface of the terrace, another parallel alignment of solid oak planks was discovered. These planks were cut from very large trees, at least 100 years old, and were pruned to a point at their ends, which were then sunk vertically into the gravel of the alluvial terrace without prior trenching. Towards the middle of the 1st c., the eastern part of the dock was rebuilt with the help of very solid, high-density piles placed in a trench filled with gravel. These posts were spaced about 2 m apart and were planted very deeply, as is demonstrated by their height, often measuring over 2 m. The elevation of this portion of the dock is very poorly preserved, but medium sized limestone blocks, assembled at the base of the wooden pieces to form a solid external facing, remain visible. This dock was levelled and was covered by a series of archaeological layers, corresponding to different periods and whose end date would not appear to have been later than the third quarter of the 1st c. Concomitantly, a previously built structure was doubly reinforced with new posts. Twenty years later, around AD 70, a new row of piles secured to planks was built between the dock and the doubled structure described above, leaving a gap of barely 3 m between these different installations. On the upper part of the embankment, 15 m to the north of the dock line, a hangar-type building was discovered, the southern façade of which measures approximately 3.80 m in width, while its length remains unknown. The structure was comprised of massive posts, with a diameter of about 0.30 m, anchored at a depth of more than 1 m in the substrate, suggesting that the building was relatively tall. The earthen floor provided ceramic elements of material culture from the Augustan Age and an oak post, which still had its bark. The latter provided a precise dendrochronological dating with a felling date of 15 BC. Thus, the building appears to slightly predate the construction of the first dock. It was in use for a very short period of time only, as it had already been levelled when a palisade was erected on this site some fifteen years later. This is probably related to the regular flooding of the river bank during the first half of the 1st c. AD. In the northern part of the Théâtre des Arts metro station, 20 m north of the palisade, a well was discovered. It was built during the Augustan Age, as confirmed by dendrochronology and the study of the ceramic material goods. The entirety of the backfill, despite being water soaked, was taken back to the lab for study (carpology, entomology and zoology). The study concluded that this was likely an open environment (perhaps a meadow) where farm animals lived, and was located close to a habitat. A few levels of human occupation were also observed in this area. These vestiges could only be very briefly observed, as they were discovered during the construction of an underground car park, following the excavation of the northern portion of the town square. This discovery consists of a wall, located precisely at the level of an interruption of the slope of the bank, and which traversed the entire area from east to west, over a length of more than 40 m. It was built of large stones, measuring about 0.50 m in width, and mounted in a dry-stone manner. At the rear, large beams laid flat, one beside the other, rested on wooden piles and formed a kind of decking. This was attributed to the second half of the 1st c. AD and represents all that we know about this discovery because this dock and the adjoining marshy area were massively filled in at the beginning of the 2nd c. AD. A large domus with private thermal baths was built to the north of the square and, during the 2nd c., a vast building of more than 450 m2, including three large rooms with a dirt floor and walls measuring 0.90 m in diameter was added. The masonry was comprised of small limestone units alternating with rows of brick. Covering, in part the stone dock, these rooms have been interpreted as storage spaces, which would have been associated with another unknown dock, built further south. The very short distance separating these spaces from the domus may suggest that its wealthy owner was linked to important trade exchanges, although there is no direct evidence to prove this. In the southern part of the Place de la Haute-Vieille-Tour, a little closer to the Seine River than the previous excavation, two discoveries were made, one in 1902 and then again in 1956. Poorly defined, they may belong to later port installations. The same applies to the old discoveries made in the Rue Grand Pont. Considering the presence of a dock and storerooms in the eastern portion of the town, another dock and riverbank reinforcement efforts in the west, as well as remains located between the two, which could be assimilated with components of a port, it would appear that the whole bank of the Seine River alongside the town was ultimately developed for port purposes. The creation of at least two rows of docks in the 1st c. AD, and one during the Augustan Age, demonstrates the importance of the Seine River to the economic development of the city. It should also be noted that the construction of the dock at the Théâtre des Arts metro station appears to be contemporary with the first dwellings excavated on the terrace of the town center. The development of the port in the 2nd c. is attested to only through the remaining vestiges of the construction of large warehouses. Without a doubt, the latter played an important role throughout the Roman period. Several epigraphic inscriptions from the second half of the 2nd c. or the beginning of the 3rd c. AD regarding the inhabitants of Rotomagus bear witness to this. One of them, discovered in Lyon, illustrates a linen merchant, a member of the utricularius of this city. On two others, discovered in the Netherlands and in York, there figures a negotiator britannicus, a merchant trading in Brittany. These cases illustrate the role played by Rouen in the important regional trade exchanges, on the one hand with the Lyonnaise (Lyon), via the Seine-Saône-Rhône axis, and on the other with Brittany and Belgian-Gaul via the Manche-Rhine axis.